Kinerja Teknologi dan Pendapatan Usahatani Padi di Lahan Sawah Pasang Surut - Yanter Hutapea; B. Raharjo; P. Hutabarat (Seminar Nasional Lahan Suboptimal, 2020)
Hutapea Y, Raharjo B, Hutabarat P.  2020.  Technology performance and rice farming income in tidal swamp land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rice technology innovation has not been optimally applied and adopted by farmers in its development areas.It is necessary to determine priority improvements in technology assistance.Therefore, this study aims to analyze the performance of the application of technology and income of rice farming in tidal swamp. Data/information collection activities were carried out in March-April 2020.The case study conducted in Pinang Banjar Village, Sungai Lilin Sub District, Musi Banyuasin Regency.Information was collected from two farmer groups, namely Banjar Sari and Banjar Harum II, with a total of 20 and 18 farmers, respectively, who are involved in Innovation-Based Agricultural Area activities.Data were analyzed descriptively both qualitatively and quantitatively, assisted by the use of Cartesian diagrams.Financial analysis was carried out to determine the feasibility level of farming in 2019 dry season and 2019/2020 rainy season.The results of the study show that based on the understanding and reality of the application of technology, the drying of grain and the use of new variety  needs improvement in its application. Farmers' understanding and its application need to be improved in irrigation, fertilization, land management, pest and disease management and the use of organic matter.The productivity of rice in Pinang Banjar Village still has the opportunity to be increased both in the rainy and dry seasons, because the results obtained have not reached half of the potential production of current superior varieties.This low productivity also results in low income for rice farming, which only reaches Rp. 5,150,600 / ha in the rainy season.